The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13104-019-4520-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in febrile cancer patients in Uganda

Abstract: Objective The aim of this study was to determine the predominant bacterial species causing bacteremia among febrile cancer patients, and their antibacterial resistance profiles at the Uganda Cancer Institute. Results We enrolled in-patients with a documented fever (≥ 37.5 °C). Bacteria from positive blood cultures were identified using standard methods biochemically. Antibacterial susceptibility testing was performed with the Kirby–Bauer disc diffusion method. From a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
43
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 25 publications
11
43
3
1
Order By: Relevance
“…In this study, 16.4% of patients suffering from hematological and solid organ malignancies had BSI which was lower than the previous study by Obeng-Nkrumah et al 3 from Ghana who reported the BSI in 22% of cancer patients and higher than the report by Lubwama et al 15 from Uganda who showed the BSI in 14.1% of cancer patients.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study, 16.4% of patients suffering from hematological and solid organ malignancies had BSI which was lower than the previous study by Obeng-Nkrumah et al 3 from Ghana who reported the BSI in 22% of cancer patients and higher than the report by Lubwama et al 15 from Uganda who showed the BSI in 14.1% of cancer patients.…”
Section: Discussioncontrasting
confidence: 78%
“…Similar findings have been reported by various authors from different parts of the world. 3,[20][21][22][23][24][25][26][27][28] However, there is no specific explanation for this finding. The most common age group of patients in this study was 0 to 10 years which is in agreement with the study conducted by Kamonrattana et al 28 More number of FN patients in our study, had underlying hematological as compared with nonhematological malignancies (solid tumors).…”
Section: Discussionmentioning
confidence: 99%
“…Similar trend has also been reported by several other studies. [23][24][25]27,32 Varying resistance to different antibiotics was observed among gram-negative and positive bacteria, respectively. Among gram-negative bacilli, percentage resistance to aminoglycosides, β-lactam/β-lactamase inhibitor combinations, fluoroquinolones, cephalosporins, carbapenems, chloramphenicol, ampicillin, co-trimoxazole, and doxycycline was 26.6 to 91.7%, 8.3 to 86.6%, 10 to 66.7%,13.3 to 73.3%, 8.3 to 73.3%, 80 to 93.3%, 13.3 to 20%, 16.7 to 66.6%, and 13.3 to 16.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among a subset of 23 studies that contained data on 3690 Gram-positive BSI cases, the MRSA isolation rate in Gram-positive bacteria was 10% (95% CI 6-14%) (5,13,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(48)(49)(50). In 15 studies whose number of S. aureus was more than 10, the pooled prevalence of MRSA among S. aureus was 44% (95% CI 32-57%) (5,13,29,33,35,37,39,(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Prevalence Of Mrsa-bsismentioning
confidence: 99%